2015
DOI: 10.1080/10894160.2015.969127
|View full text |Cite
|
Sign up to set email alerts
|

Pride and Prejudice: Factors Affecting School Attachment Among Lesbian, Bisexual, and Heterosexual Girls

Abstract: School attachment is often regarded as a key measure in gauging the integration and wellbeing of students. Previous research suggests that levels of school attachment are generally lower among sexual minority students, but most studies focus on between-gender comparisons and do not conduct within-gender analyses. Using data from the First National Climate Survey on Homophobia and Transphobia in Canadian schools, this study set out to empirically analyze what, if any, differences exist among lesbian, bisexual, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Girls experience persistent gender-based discrimination, regardless of sexual orientation (Szymanski & Henrichs-Beck, 2014). Sexual minority girls report gender-negative language that is related to, but distinct from, homophobic slurs (Peter, Taylor, Ristock, & Edkins, 2015). Studies of sexual minority women indicate that heterosexism and sexism were distinct distress predictors (Szymanski & Henrichs-Beck, 2014).…”
Section: The Role Of Gendermentioning
confidence: 99%
“…Girls experience persistent gender-based discrimination, regardless of sexual orientation (Szymanski & Henrichs-Beck, 2014). Sexual minority girls report gender-negative language that is related to, but distinct from, homophobic slurs (Peter, Taylor, Ristock, & Edkins, 2015). Studies of sexual minority women indicate that heterosexism and sexism were distinct distress predictors (Szymanski & Henrichs-Beck, 2014).…”
Section: The Role Of Gendermentioning
confidence: 99%
“…Thus, even at its lowest point (i.e., 2SLGBTQ + students during the first wave of the pandemic with low PI), students with high SA did better than participants with low SA and high PI. Other research shows the key role of school attachment, which is generally lower among 2SLGBTQ + students (Poteat et al, 2011;Peter et al, 2015). For instance, research has found that 2SLGBTQ + students' sense of school belonging mediates the relationship between peer victimization and depression (Hatchel et al, 2018) and lowers suicidal ideation and attempts (Bariola et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, research has found that 2SLGBTQ + students' sense of school belonging mediates the relationship between peer victimization and depression (Hatchel et al, 2018) and lowers suicidal ideation and attempts (Bariola et al, 2017). Unsurprisingly, experiences of discrimination and harassment in school lowers 2SLGBTQ + students' school attachment (Diaz et al, 2010;Peter et al, 2015;Hatchel et al, 2019), which negatively impacts students' grades, attendance, Pre-Pandemic and pandemic slopes between parental involvement and positive mental health by level of school attachment among 2SLGBTQ + students.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the current results, it is not appropriate to assert that LGBTQ women are less likely to experience prejudicerelated stressors compared to LGBTQ men. As numerous Canadians studies demonstrate, LGBTQ females can be even more likely to experience various forms of discrimination than both LGBTQ and CH men, as well as CH women (Taylor et al, 2011;Peter et al, 2015;Saewyc et al, 2007).…”
Section: Discussionmentioning
confidence: 99%